PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN EDUCAPLAY PADA MATA PELAJARAN BAHASA INDONESIA KELAS V SDN 04 PULAU PUNJUNG - Septa Tri Rahmat; Feby Kharisna; Ratnawati (Jurnal Tunas Pendidikan, 2025)
Research on the development of learning media assisted by Educaplay in the Indonesian Language subjects for class V of SDN 04 Pulau Punjung aims to evaluate the validity, practicality, and effectiveness of Media Assisted by Educaplay in learning Indonesian Language Fiction and Non-fiction material for class V students. Subjects the research subjects consisted of 20 students at SDN 04 Pulau Punjung. The method used is research and development (R&D) with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. Data collected data collected includes quantitative and qualitative data through validation tests of materials, media, questions, teaching modules and language, as well as a practicality questionnaire filled out by teachers and students. The trial was conducted on small and large groups. Validation results validation results showed that the average material validation reached 93,2%, media validation 93%, question validation 93% teaching module validation 92,7%, and language validation 93%, all of which are included in the “Very Valid” category. The practicability of Educaplay Assisted media based on teacher and student responses reached 92,98% indicating the “Very Practical” category. In addition, the effectiveness of this interactive learning media obtained a value of 81% which is also classified as “Very Effective”. Effective”. With the existence of Educaplay Assisted learning media it can help students in learning.